Antibacterial and Antifungal Activities of Essential Oils Extracted from Medicinal Plants Using CO2 Supercritical Fluid Extraction Technology - Asif Hanif, Muhammad; Nawaz Bhatti, Haq; Salman Jamil, Muhammad; Salman Anjum, Rana; Jamil, Amer; Mumtaz Khan, Muhammad (Asian Journal of Chemistry, 2010)
Antibacterial and antifungal activities of 110 medicinal plants most commonly used in Pakistani medicine were determined by zone inhibition method. The essential oils from medicinal plants were extracted using CO2 supercritical fluid extraction technology. The oils were subsequently purified under reduced pressure to avoid degradation of their components. Strongest Bacillus subtilis inhibition was shown by Petrocarpus santalinus, Valeriana officinalis, Caryophyllus arometicus, Trapa bispinosa and Mentha arrivensis. Whereas, strongest Ganoderma luciderm inhibition activity was shown by Mentha arrivensis, Hibiscus esulentus and Acacia concinna. Many medicinal plants have not shown any inhibition activity against Bacillus subtilis and Ganoderma lucidum. Results of the present study can be very helpful in evaluating the mechanism of action of essential oil extracted from medicinal plants using CO2 supercritical fluid extraction technology.